IMPLIKASI PEMBERLAKUAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. EXXON MOBIL OIL INDONESIA DI ACEH UTARA - Hutabarat, Sonya Theresia; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to find about the implications of CSR are implemented by ExxonMobil towards in North Aceh. ExxonMobil has operations in North Aceh since 1968 and became Cooperation Contract between Pertamina and also LNG Japan. ExxonMobil is one of the multinational companies which in this case is not performing CSR as provided by law.This research used concepts on CSR, which is proposed by John Elkington is very relevant to the case discussed in this research. This research shows that ExxonMobil has long operated in North Aceh not contribute to enhancing the quality of life in North Aceh even cause imbalance, besides it also ExxonMobil has damaged the environment and also the residence of the people of Aceh. People are also threatened his health with ExxonMobil exploration activities are not friendly environmentally .Keywords: Implication, CSR, ExxonMobil, North Aceh